An Assessment of Parental Knowledge, Belief and Attitude toward Childhood Immunization among Minorities in Rural Areas of District Faisalabad, Pakistan - Asim, Muhammad; Malik, Nazia; Yousaf, Haroon; Gillani, Iram; Habib, Nazeen (Mediterranean Journal of Social Sciences, 2012)
Childhood immunization protects children from a variety of serious and potentially fatal and life threateningcommunicable diseases. Now immunization of children has been one of the securest and most efficient measures againstavertable diseases in all over the world including Pakistan. In many societies where more than one racial, ethnic and religiousminorities group exist, and one group is Inclined to dominant the others. This generally conduces to social and economicdisfavor for the secondary groups. That’s why this study was designed to explore the gap toward health facilities and assess theparental knowledge, belief and attitude toward childhood immunization. A sample of 160 Christian minorities was selectedconveniently from District Faisalabad through multistage sampling techniques. Majority of the respondents 95% were aware ofchild immunization, and 81.3% respondents agreed that child immunization were impotent for the children for their healthy future.85% of the respondents were in the opinion that childhood immunization is more beneficial than harmful, and 90% of therespondents confessed that child immunization is not prohibited in our religion.